Melatonin: Current status and future perspectives in horticultural plants - Zhao, Jing; Hu, Junjie (Frontiers in Plant Science, 2023)
Amid various threats to food security around the world, the abiotic stresses are eminent ones, which are increasing with elevating global warming, and causing restrictions to plant growth and development. Different phytohormones are produced by plants for mitigating the adverse effects of these stresses. One such phytohormones is melatonin (MT), which being a potential bio stimulator, helps to govern a wide array of functions in horticultural crops. Recent advancements has determined the role of MT in plants while responding towards abiotic stresses. MT enhanced physiological functions such as seed germination, growth and development, seedling growth, root architecture system, photosynthetic efficiency. The exceptional antioxidant properties of MT under stressful environments helps to increase the enzymatic and non-enzymatic activities of antioxidants, thus playing role in substantial scavenging of reactive oxygen species (ROS). Additionally, MT as a plant growth regulator and bio-stimulator aids in promoting plant tolerance to abiotic stress, mainly through improvements in nutrient uptake, osmolytes production, and cellular membrane stability. Current review, thus, aims to elaborate the possible functions of MT under different abiotic stress conditions in horticultural crops, which would be beneficial for learning about MT in details under altering environments, and highlighting the strand of literature for development of stress tolerance in horticultural crops.